Development of Canva-Based "PANDERA" Learning Media to Enhance Elementary Students’ Understanding of the Five Human Senses - Gunadi, Radila Putri; Sujana, Atep; Ismail, Ali (Jurnal Pendidikan Progresif, 2025)
Development of Canva-Based "PANDERA" Learning Media to Enhance Elementary Students’ Understanding of the Five Human Senses. The topic of human senses is a crucial component of the fifth-grade elementary school curriculum. However, due to its abstract nature, it can be challenging for students to grasp. The use of technology in education has brought significant changes in the way of teaching and learning. Therefore, innovative learning media are essential to enhance students' understanding and make the material more accessible. Objectives: This study aims to validate and evaluate the PANDERA learning media, or the Canva-based Human Senses application, designed for fifth-grade elementary school students. Methods: This study employs a research and development (R&D) approach, utilizing the ASSURE model, which consists of six stages: Analyze Learners, State Objectives, Select Methods, Media, or Materials, Utilize Media and Materials, Require Learner Participation, and Evaluate. Findings: The expert validation results in the form of assessments of aspects of material, design, content and learning obtained an average score of 4.7, based on the ≥ 4 category, the PANDERA learning media was classified as feasible (valid). Meanwhile, the implementation results for fifth-grade students showed an average pretest score of 48.57 and a posttest score of 84. Statistical analysis results of the paired sample t-test, the Sig. (p-value) was found to be 0.01, which is Sig. (p-value) < 0.05. This indicates a significant difference before and after using the PANDERA learning media. Conclusion: Based on the research findings, it can be concluded that the PANDERA learning media, developed using the Canva application for the human senses topic, is effective and can be used to enhance the understanding of fifth-grade elementary school students. Keywords: learning media, canva application, five human senses.